Explaining structural changes towards and within the financial sector - Sabrina Studer; Josef Falkinger; Yingnan Zhao (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper presents a 3x3 general equilibrium model of an OLG-economy with financial intermediaries, technological uncertainty, heterogeneous agents with quasi-homothetic preferences to analyze structural change between the real and the financial sector as well as within the financial sector. Besides the consumption and investment good two types of financial services are produced. The financial services support agents in choosing their investment strategy and managing their portfolios. The three factors of production are: Capital, skilled and unskilled labor. The financial market provides deposits and an incomplete set of securities. Payoffs of assets are determined by the future profitability of the technologies in which they are invested. We show that structural change is generated by rising per-capita income, by an increase in inequality, stronger market power of firms or directed technical change. In turn, structural change can raise inequality. We identify conditions under which a self-feeding circle between inequality and structural change with respect to finance emerges.
Keywords: O16; J31; D90; 330